1985
DOI: 10.1161/01.atv.5.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Platelet and megakaryocyte changes in cholesterol-induced experimental atherosclerosis.

Abstract: Rabbits were fed either 2 g cholesterol in 10 ml olive oil daily with normal diet (n = 5) or normal diet alone (n = 5). After 12 weeks, the cholesterol-fed animals had developed fatty plaques involving 24% ± 4% of the surface area of the aorta; the control animals had none. Mean platelet volume was significantly smaller (p < 0.04) in the cholesterol-fed animals (4.1 ± 0.3 fl) compared with the controls (4.8 ± 0.4 fl). The heterogeneity of the average volume distributions of the two groups, characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 21 publications
(16 reference statements)
0
19
1
Order By: Relevance
“…It has also been demonstrated in rabbits and guinea pigs that similar changes in MK size and ploidy can be induced by feeding animals a high cholesterol diet for prolonged periods of time [56,57]. Furthermore, acute destruction of platelets with an anti-platelet serum in rabbits fed a high cholesterol diet led to a further increase in the size and DNA content of MKs and to an acceleration of atherogenesis (Fig.…”
Section: Increase In Megakaryocyte Ploidy May Have a Role In Myocardimentioning
confidence: 77%
“…It has also been demonstrated in rabbits and guinea pigs that similar changes in MK size and ploidy can be induced by feeding animals a high cholesterol diet for prolonged periods of time [56,57]. Furthermore, acute destruction of platelets with an anti-platelet serum in rabbits fed a high cholesterol diet led to a further increase in the size and DNA content of MKs and to an acceleration of atherogenesis (Fig.…”
Section: Increase In Megakaryocyte Ploidy May Have a Role In Myocardimentioning
confidence: 77%
“…Animal models with a high cholesterol diet show a significant increase in the PLT count compared to those fed the normal diet 19) . The positive correlation between the PLT count and LDL-C level and multiple metabolic factors reported in population studies suggests a potential link between the PLT count and dyslipidemia 1,2) .…”
Section: Discussionmentioning
confidence: 98%
“…Atherogenic lipoproteins -low-density lipid (LDL) and very low-density lipid cholesterol -enhance platelet activation in vitro [3][4][5] and increase platelet cholesterol. Previous studies using animal models have shown that increased platelet cholesterol is due to the uptake of circulating cholesterol by megakaryocytes which then incorporate into future platelets [6,7] .…”
Section: Introductionmentioning
confidence: 99%